2019
DOI: 10.3390/ijgi8020063
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Visualization Techniques and Methods of Moving-Object-Trajectory Data: A Review

Abstract: Trajectory big data have significant applications in many areas, such as traffic management, urban planning and military reconnaissance. Traditional visualization methods, which are represented by contour maps, shading maps and hypsometric maps, are mainly based on the spatiotemporal information of trajectories, which can macroscopically study the spatiotemporal conditions of the entire trajectory set and microscopically analyze the individual movement of each trajectory; such methods are widely used in screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 130 publications
(200 reference statements)
0
16
0
Order By: Relevance
“…The network identifies with great accuracy the rate changes of speed and trajectories on routes, being able to adjust the GPS parameters in factors of similarity for the adequate detection of transport mode. In He, et al [65] performs a review on the formal methods for the recollection of GPS data and detection of modes of transport proposing a methodology of Acquisition, filtering and data processing a through android platforms and the possible algorithms for detecting modes of transport. His proposal offers a panorama of system from the client's perspective and other of the server and the system is based on processes in real time and how they could be optimized algorithms and energy consumption in the smartphones.…”
Section: Data Mining Approachmentioning
confidence: 99%
“…The network identifies with great accuracy the rate changes of speed and trajectories on routes, being able to adjust the GPS parameters in factors of similarity for the adequate detection of transport mode. In He, et al [65] performs a review on the formal methods for the recollection of GPS data and detection of modes of transport proposing a methodology of Acquisition, filtering and data processing a through android platforms and the possible algorithms for detecting modes of transport. His proposal offers a panorama of system from the client's perspective and other of the server and the system is based on processes in real time and how they could be optimized algorithms and energy consumption in the smartphones.…”
Section: Data Mining Approachmentioning
confidence: 99%
“…Increasing walkability, reducing traffic congestion, or identifying underused infrastructure, all these objectives may require different data collection methods and analyses. Moreover, the inherent complexity and spatio-temporal nature of the data calls for effective visualizations to extract meaningful information [29]. In this study, we demonstrated the potential of webcams, an inexpensive and easy-to-use technology to study the current use of public spaces and to evaluate any ongoing changes.…”
Section: Discussionmentioning
confidence: 86%
“…Although including the temporal component of the webcam data makes its analysis and visualization much more challenging [26], it provides a more complete picture of the urban dynamics. Space-time cube (STC) representation has proved to be useful means of conceptualization, analysis and visualization of spatio-temporal events [27,28] and trajectories [29]. It has been used for characterizing various urban phenomena, including crime hotspots [30], urban fires [31], and dengue fever [32], as well as for studying human activity patterns [33,34] and describing big trajectory datasets [35,36].In this paper, we build on a previous study by Hipp et al [25] and present a new method to derive high-resolution spatio-temporal pedestrian density from webcam images.…”
mentioning
confidence: 99%
“…Recent surveys on big spatiotemporal data by Yang et al [11] and He et al [12] argue that most of the existing tools for visual exploration serve a single specific use case, acknowledging the need for more flexible data visualization approaches that allow users to examine the behavioral changes in the information over the temporal and spatial domains while having sensible storage requirements and improving query performance. The approach described in this paper has been precisely formulated to comply with those requirements, considering smart cities as a meaningful use-case scenario.…”
Section: Related Workmentioning
confidence: 99%